Integration of the Madrasah Diniyah Curriculum with the Nature School Curriculum - Firdhausyah, Ananda Ammathul; Rohman, Nurur; Putri, Candra Avista; Susilawati, Samsul (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The madrasah diniyah curriculum is a curriculum that can be integrated with the natural school curriculum. The background of the madrasah diniyah and the natural school is an important factor in the development of the curriculum in the school. The purpose of this study is to describe the background of the integration of the madrasah diniyah curriculum with the natural school curriculum, and explain the model of integration of the madrasah diniyah curriculum with the natural school curriculum. This study uses a qualitative approach, namely the type of case study research. Research data were collected from observations, interviews, and documentation. Then the collected data in the form of field notes and documentation were analyzed by means of reduction, data presentation, and drawing conclusions. The results of this study are the background of the integration of the madrasah diniyah and natural school curriculum including philosophical and practical aspects, and the model of integration of the madrasah diniyah and natural school curriculum to create a figure who has logical leadership morals, requires an integrative-interconnective scientific structure and integration of the madrasah diniyah tradition with the application of ubudiyah daily habits.